ANALYSIS OF THE NEEDS OF USING VIDEO MEDIA IN MATHEMATICS LEARNING FOR GRADE VI ELEMENTARY SCHOOL STUDENTS - Eva Solina; Somakim; Farida R Wargadalem (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the needs of students and educators for mathematics learning media that are in accordance with the characteristics of elementary school students and contextual approaches such as PMRI (Indonesian Realistic Mathematics Approach). The main problem raised in this study is the low interest and understanding of students in mathematics material caused by the lack of use of interesting learning media. The method used in this study is a descriptive method with a quantitative approach. Data collection was carried out by distributing questionnaires using Google Form to 30 grade VI students and 3 teachers at SD Negeri 3 Babat. The questionnaire instrument was designed to measure various aspects of the needs of students, educators, and learning media. The results of the analysis showed that students wanted media that was relevant (100%), interactive (98.55%), visually appealing (100%), helped understanding (100%), and was short in duration (97.05%). Meanwhile, educators assessed all aspects of the learning media proposed in the questionnaire as important and very much needed with a percentage of 100% for all indicators, including suitability with the PMRI approach, ease of access, and the existence of practice questions. This result is also supported by the analysis of media needs which shows a percentage of 100% in all indicators. This finding is an important basis for the development of more effective learning media and in accordance with real needs in learning mathematics in elementary schools.